Evaluasi Kualitas Fungsional Aplikasi Point of Sales (POS) Restoran Berbasis Web (Open Source) Menggunakan Standar Pengujian ISO/IEC 29119 - Muhamad Raehan; Alanjono Astian Jondy; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
The utilization of open-source software from public repositories like GitHub serves as an efficient solution for the digitalization of culinary MSMEs. However, the lack of formal testing documentation in open-source projects often raises concerns regarding system stability, logic accuracy, and data security. This study aims to conduct a comprehensive audit and functional quality evaluation of a web-based Restaurant Point of Sales (POS) application (built with Native PHP and MySQL) sourced from a GitHub repository. This research does not focus on system development but rather on verifying system feasibility using the international standard ISO/IEC 29119-3. The applied method is Black Box Testing to validate system output against user input. Equivalence Partitioning and Boundary Value Analysis techniques were employed to design 27 test cases covering interface validation, transaction arithmetic accuracy, and database data integrity (ACID). The test execution results indicated that the application successfully handled all test scenarios with a "Pass" status (100% success rate). No bugs or software defects (Zero Defect) were found in critical functions. This study concludes that the open-source POS application possesses high logic stability, is free from critical functional errors, and is declared feasible for implementation in a real production environment.